Analyze the inefficient takt time production and high customer complaint for support wheel carrier component to improve Lean production system level at Autokeen Sdn.Bhd - Abd Rahman Fahmi, Mat Hasan (2012)
This project presents a research to analyze the inefficient takt time production and high customer complaint for support wheel carrier part to improve level of Lean Production System (LPS) at Autokeen Sdn Bhd.The case study method has been conducted at Autokeen Sdn Bhd especially at support wheel carrier workstation.The main purpose of this research is to give the recommendation to improve the takt production and customer complaint criteria in Autokeen LPS evaluation. From the research,the finding shows that the process cycle time for produce support wheel carrier is over the customer takt time.This problem because the customer takt time never being calculates and be display at support wheel carrier workstation. For the customer complaint criteria,many cases of defect part are delivering to customer because of man power carelessness.After all problems root causes being analyze the recommendation is given to improve the criteria of takt production and customer complaint.